A Streetcar named desire - Kazan, Elia.; Leigh, Vivien 1913-1967.; Brando, Marlon; Hunter, Kim 1922-2002.; Malden, Karl.; Williams, Tennessee 1911-1983.; Charles K. Feldman Group Productions; Warner Bros. ([S.l.] Warner Home Video (Phils.), 1994)
Blanche is in real need of protector stage in her life when circumstances lead her into paying a visit to her younger sister Stella in New Orleans. She doesn't understand Ahow Stella, who is expecting her first child, could have picked a husband so lacking in refinement. Stanley Kowalski's buddies come over to the house to play cards and one of them, Mitch, finds Blanche attractive until Stanley tells him about what kind of a woman Blanche really is. What will happen when Stella goes to the hospital to have her baby and just Blanche and her brother-in-law are in the house?
Based on the original play by Tennessee Williams.
Originally released as motion picture in 1951.
"Original director's version, totally restored footage never seen before"--Container.
Summary from the website: http://www.imdb.com/title/tt0044081/plotsummary
Screenplay, Tennessee Williams ; music, Alex North.
Vivien Leigh, Marlon Brando, Kim Hunter, Karl Maiden.
Keywords: Man-woman relationships -- Louisiana -- New Orleans -- Drama; Neurotics -- Drama; Feature films